KNOWLEDGE AND ATTITUDES ABOUTPREMARITAL SEX IN SMK N 3 KLATEN - Dwi Lestari; Murwati .; Putri Kusumawati Priyono (STIKES DUTAGAMA KLATEN, 2015)
Background: Sex outside of marriage and adversely affected and the actors themselves around. The impact of which the possibility of contracting sexually transmitted diseases and pregnancy outside marriage. It is also impact the high rate of abortion.Each year there are approximately 2.3 million abortions in Indonesia, where 20 percent of teenagers do. Objective: To describe the knowledge and attitudes about premarital sex teens in SMK N 3 Klaten. This study uses descriptive and cross-sectional design of the study. The population in this study as many as 332 students. The amount of samples taken in this study was 96 students. The sampling technique used Probability Sampling Techniques. Research Methods: Respondents had knowledge about premarital sex in the category of good knowledge that by 82 students (85.4%), respondents are included in the category quite as many as 12 students (12.5%) and much less category 2 students (2.1%). Attitudes about premarital sex in the negative category were 63 students (65.6%), respondents in the positive category 33 students (34.4%). Results: illustrate that teens about premarital sex knowledge in SMK N 3 Klaten is 85.4% included in both categories and teen attitudes about premarital sex was 65.5% in the negative category.